2015
DOI: 10.1007/s00216-015-8793-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of indirect methods for the determination of deoxynivalenol and its conjugated forms in cereals

Abstract: A critical assessment of three previously published indirect methods based on acidic hydrolysis using superacids for the determination of “free” and “total” deoxynivalenol (DON) was carried out. The modified mycotoxins DON-3-glucoside (D3G), 3-acetyl-DON (3ADON), and 15-acetyl-DON (15ADON) were chosen as model analytes. The initial experiments focused on the stability/degradation of DON under hydrolytic conditions and the ability to release DON from the modified forms. Acidic conditions that were capable of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…The hydrolysis procedure was considered by these authors as a cheaper and simpler alternative to determine total DON-conjugated mycotoxins in cereals, especially because it uses quantification by ELISA kits. However, Malachová et al (2015) recently published a critical evaluation of these indirect methods for total DON-conjugated determination, raising doubts on their efficacy as, according to these authors, none of them were able to release DON from its conjugated form, and for this reason, they were not recommended for such evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrolysis procedure was considered by these authors as a cheaper and simpler alternative to determine total DON-conjugated mycotoxins in cereals, especially because it uses quantification by ELISA kits. However, Malachová et al (2015) recently published a critical evaluation of these indirect methods for total DON-conjugated determination, raising doubts on their efficacy as, according to these authors, none of them were able to release DON from its conjugated form, and for this reason, they were not recommended for such evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the bioavailability of D3G is probably low compared to that of DON, as human Caco-2 cells do not absorb D3G [ 33 ]. Although D3G is highly resistant to acidic hydrolysis [ 34 ], it can be enzymatically hydrolyzed by intestinal bacteria [ 35 ] and the released DON may be (partially) absorbed in the distal part of the gut. It was shown that D3G is indeed effectively hydrolyzed in the digestive tracts of humans and animals [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors pointed out that hidden fumonisins could be embedded to starch or proteins of the matrix. Respecting DON, alkaline conditions cause a transformation of 3-acetyldeoxynivalenol (3-ADON) and 15-acetyldeoxynivalenol (15-ADON) to DON (Malachova, Stockova, Wakker, Varga, Krska, Michlmayr, et al, 2015). These authors showed that 32 % of 3-ADON and 47 % of 15-ADON in flour matrix were hydrolysed to DON when samples were submitted to KOH treatment.…”
Section: Alkaline Treatmentmentioning
confidence: 99%
“…These authors showed that 32 % of 3-ADON and 47 % of 15-ADON in flour matrix were hydrolysed to DON when samples were submitted to KOH treatment. This was caused by the presence of additional (unknown) sources of DON in the sample (Malachova, et al, 2015). Some DON could be hidden in starch or proteins of the matrix like fumonisins.…”
Section: Alkaline Treatmentmentioning
confidence: 99%